Bullying in Elementary School: An Analysis of The Film Wonder (2017) - Shima Sari Dewi Fatimah (Universitas Pendidikan Indonesia (UPI), 2021)
Different genres are used to address bullying as a social problem. This research investigates bullying in a film, Wonder (2017) which uses an elementary school as the locus of the story. The research aims to determine how the film depicts bullying in an elementary school and what messages are conveyed from the presentations. The researcher uses Coloroso's (2015) theory of bullying and Boggs Petrie's (2008) theory of characterization in films to analyze the presentation of bullying in films and the messages conveyed from the presentation. The research discovered that there are three types of bullying depicted in the film. They are verbal, physical, and relational bullying. The findings indicate that bullying does happen in elementary schools, the bullying victim tends to remain silent, and people around the victim tend to ignore the occurrence. The film suggests that bullying is an issue for society to be aware of. The research then suggests that this kind of issue should be addressed in other literary genres as bullying presentation in literary genres can be used as the tool for learning the ways to solve bullying and sharing perspectives of people who are affected by bullying.